Pengaruh Green Promotion, Green Packaging, Green Physical Evidence Terhadap Keputusan Pembelian Fore Coffee Di Kota Bandung - Siti Maesarah; Sri Astuti Pratminingsih (Community Engagement and Emergence Journal (CEEJ), 2026)
This study aims to analyze the effect of green promotion, green packaging, and green physical evidence on consumer purchase decisions at Fore Coffee in Bandung. This research employed a quantitative method with descriptive and verificative approaches. The sampling technique used was non-probability sampling with a purposive sampling method. The total number of respondents in this study was 100 Fore Coffee consumers in Bandung. Data were collected through questionnaires and analyzed using multiple linear regression with IBM SPSS Statistics. The results indicate that partially, green promotion has a positive and significant effect on purchase decisions (p = 0.005). Green packaging also has a positive and significant effect on purchase decisions (p < 0.001) and is the most dominant variable. Meanwhile, green physical evidence has no significant effect on purchase decisions (p = 0.315). Simultaneously, green promotion, green packaging, and green physical evidence significantly affect purchase decisions (p < 0.001). The coefficient of determination shows that the three independent variables explain 60.9% of purchase decisions, while the remaining 39.1% is influenced by other factors outside this study. These findings indicate that green marketing strategies, particularly green promotion and green packaging, play an important role in encouraging consumer purchase decisions at Fore Coffee.